The predominance of social proximity for innovation collaboration of SME - Sidonia von Proff (Philipps-University Marburg, Department of Geography, 2016)
The paper at hand contributes to the field of proximity studies with a focus on social proximity. The paper gives an in-depth discussion of a theoretical and empirical definition of social proximity. Based on this, an argumentation follows why social proximity is of particular importance when the decision for external innovation collaboration partners has to be made. This holds especially for SME and for firms with low or medium innovativeness. Furthermore, the paper presents two explorative case studies as a first support for the developed theory. The analysis of two firms shows how social proximity guides the search for collaboration partners.
Keywords: L14; O39; O32; 330; Social proximity; innovation collaboration; SME